The mediating role of perceived social support: alexithymia and parental burnout in parents of children with autism spectrum disorder - Lin, Yuanting; Wang, Yan; Lin, Chunhui; Ni, Qingnan; Jia, Ruolin; Chang, Yanling; Qi, YuanPing (Frontiers in Psychology, 2023)
Background: Parental burnout is a concept that reflects the emotional exhaustion and emotional distance of parents from children due to their inability to cope with the pressure of parenting. It has been confirmed that parents of ASD children are at higher risk for parental burnout. Additional research has suggested a relationship between parental burnout and parents' personality traits. However, the relationship between alexithymia, an independent personality factor, with parental burnout is little to none. Objective: To look into the connection between parental burnout and alexithymia among parents of children with ASD. Method: 301 parents were approached for recruitment and data were collected from 203 parents through a cross-sectional survey assessing parental burnout, alexithymia status, and perceived social support. Because the data is not normally distributed, Spearman's rank correlation coefficient rho(p) was used to assess the correlation between the variables; and then using AMOS to analyze the mediating effects of perceived social support and the moderating effect of gender. Result: The result showed that 1) There’s a negative association between alexithymia with parental burnout (β=0.6, p<0.01), while perceive social support was the negative predictor of alexithymia (β= -0.45, p < 0.01) and parental burnout(β= -0.26, p < 0.01); 2) perceive social support partially mediated the relationship between alexithymia and parental burnout of parents with ASD children, which can explain 16.3% of the total effect; 3) Gender plays a moderating role in the first half of the indirect effect of alexithymia on parental burnout, as evidenced by the significant difference in path coefficients between the male and female models(male:β=-0.10, p＜0.05; female:β=-0.60, p＜0.05). Conclusion: Health professionals and policymakers should be aware of parental burnout among parents of autistic children in China and take early intervention steps. Futhermore, they should recognize the negative impact of alexithymia and the positive impact of social support when developing plans to alleviate parental burnout in children with autism, with a particular focus on mothers with alexithymia, who are more likely to experience low social support and burnout than fathers with alexithymia.